Live online training : 90 minutes on moving through crisis to recovery - Owens, Cynthia (O'Reilly Media, 2020)
"Rarely does a crisis touch so many people so fast. Managing people right now has become even more complicated and more challenging, but there are things you can do to set your organization and your team up to weather this crisis. Expert Cynthia Owens managed a team during the SARS crisis in Singapore. Over 90 minutes, she'll share what she learned and actions you can take at each of the three stages of a crisis. Get clear takeaways for immediate action and steps to take as your organization moves from crisis to recovery. This includes how and when to communicate, ways to move quickly to virtual work, and strategies for keeping teams connected and work on track. Cynthia also touches on how to work through the practical and the emotional challenges that may arise, emphasizing that this crisis touches people in different ways."--Resource description page